Encoding colour: Capturing rule-based logic in design studio - Zafira Rahmatul Ummah; Paramita Atmodiwirjo (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
This paper argues that introducing algorithmic thinking to basic design pedagogy should give prominence to the basic logic and attitudes rather than learning the computational devices and tools. This paper examines the integration of computation or algorithmic thinking into a basic design studio in architectural education at Universitas Indonesia. The integration is conducted through a colour composing exercise that comprises four major stages: identifying patterns, rulemaking, colouring-composing, and reflection. The findings from this study demonstrate how the students are utilising algorithmic thinking as the primary reason to design their colour composition in different ways and complexity. Furthermore, the students can also point out some underlying concepts and creative strategies of design computing concerning colour composing. The findings of this study indicate the importance to promote students' understanding of computation that is not merely tools but more into design reasonings and skills.